Cell type-specific roles for Cdc42, Rac, and RhoL in Drosophila oogenesis. - Murphy, A.M.; Montell, D.J. (Journal of Cell Biology, 1996)
The Rho subfamily of GTPases has been shown to regulate cellular morphology. We report the discovery of a new member of the Rho family, named RhoL, which is equally similar to Rac, Rho, and Cdc42. Expression of a dominant-negative RhoL transgene in the Drosophila ovary caused nurse cells to collapse and fuse together. Mutant forms of Cdc42 mimicked this effect. Expression of constitutively active RhoL led to nurse cell subcortical actin breakdown and disruption of nurse cell-follicle cell contacts, followed by germ cell apoptosis. In contrast, Rac activity was specifically required for migration of a subset of follicle cells called border cells. All three activities were necessary for normal transfer of nurse cell cytoplasm to the oocyte. These results suggest that Rho protein activities have cell type-specific effects on morphogenesis.